Effects of Human Resource Investment on Economic Sustainability of Nigerian Real Estate Industry - Olajide Idowu OKUNBANJO (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2020)
The sustainability of real estate industry in Nigeria has become a challenge to the stakeholders of the industry since the arrival of globalization and this has resulted to the industry low contributions to Nigeria economic growth. Therefore, this research study investigated effects of human resource investment on economic sustainability of real estate industry in Nigeria. The study adopted ex-factor research design data collection and data were collected from the annual reports of Arbico Plc. The statistical techniques adopted were descriptive statistics with regression analysis. The findings revealed that investment in human resource of Arbico Plc has a positive and significant contribution to the firm’s economic sustainability. It was put forward that that Arbico Plc should continue to invest more on the human resource via training the employees. Also, regulatory authority on financial reporting in Nigeria should mandate all listed firms in the real estate industry to report employee training cost in their yearly annual reports.